Use of the Canadian CT head rule for patients on anticoagulant/anti-platelet therapy presenting with mild traumatic brain injury: prospective observational study - Uccella, Laura; Riboni, Cristiana; Polinelli, Francesco; Biondi, Carola; Uccheddu, Graziano; Petrino, Roberta; Majno-Hurst, Pietro (Frontiers in Neurology, 2024)
Background and importance: Mild traumatic brain injury (mTBI) is a frequent presentation in Emergency Department (ED). There are standardised guidelines, the Canadian CT Head Rule (CCHR), for CT scan in mTBI that rule out patients on either anticoagulant or anti-platelet therapy. All patients with these therapies undergo a CT scan irrespectively of other consideration. Objective: determine whether standard guidelines could be applied to patients on anticoagulants or anti-platelet drugs. Design, settings and participants: 1015 patients with mTBI and Glasgow Coma Score (GCS) of 15 were prospectively recruited, 509 either on anticoagulant or anti-platelet therapy and 506 on neither. All patients on neither therapy underwent CT scan following guidelines. All patients with mTBI on either therapy underwent CT scan irrespective of the guidelines. Outcome measure and analysis: primary endpoint was the incidence of post-traumatic intracranial bleeding in patients either on anticoagulants or anti-platelet drugs and in patients who were not on these therapies. Bayesian statistical analysis with calculation of Confidence Intervals (CI) was then performed. Main results: Sixty scans were positive for bleeding: 59 patients fulfilled the criteria and 1 did not. Among patients with haemorrhage, 24 were on either therapy and only one did not meet the guidelines but in this patient the CT scan was performed before two hours from the mTBI. Patients on either therapy did not have higher bleeding rates than patients on neither.1 There were higher bleeding rates in patients on anti-platelet therapy who met the guidelines vs patients who did not. These rates overlapped with patients on neither therapy, meeting CCHR. Conclusions: The CCHR might be used for mTBI patients on either therapy. Anticoagulants and anti-platelet drugs should not be considered a risk factor for patients with mTBI and a GCS of 15. Multicentric studies are needed to confirm this result.